2022
DOI: 10.3390/jfb13030121
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review on the Effectiveness of Bone Regeneration Procedures with OsteoBiol® Collagenated Porcine Grafts: The Translational Research Experience over 20 Years

Abstract: Over the years, several bone regeneration procedures have been proposed using natural (autografts, allografts, and xenografts) and synthetic (i.e., metals, ceramics, and polymers) bone grafts. In particular, numerous in vitro and human and animal in vivo studies have been focused on the discovery of innovative and suitable biomaterials for oral and maxillofacial applications in the treatment of severely atrophied jaws. On this basis, the main objective of the present narrative review was to investigate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 168 publications
0
9
0
Order By: Relevance
“…The results showed that aloe vera gel provided better results than CHX [ 80 ]. These studies have highlighted the mechanisms of action of aloe vera which has the following: Anti-inflammatory properties thanks to the content of acemannans and anthraquinones which can reduce inflammation by acting on inflammatory processes at a cellular level [ 103 ]; Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ]; Antimicrobial action preventing infections and helping to maintain oral hygiene [ 80 , 105 ]; Effects on bacterial plaque, influencing its growth and formation [ 106 ]; Effects on the immune system by helping to regulate the immune response and reduce inflammation [ 107 ]; Positive effects on wound healing by stimulating collagen production especially in the presence of small wounds or irritations caused by orthodontic devices [ 108 , 109 ]; Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ]. …”
Section: Discussionmentioning
confidence: 99%
“…The results showed that aloe vera gel provided better results than CHX [ 80 ]. These studies have highlighted the mechanisms of action of aloe vera which has the following: Anti-inflammatory properties thanks to the content of acemannans and anthraquinones which can reduce inflammation by acting on inflammatory processes at a cellular level [ 103 ]; Antioxidant properties thanks to the presence of vitamins C and E and flavonoids which protect cells from damage caused by free radicals [ 51 , 104 ]; Antimicrobial action preventing infections and helping to maintain oral hygiene [ 80 , 105 ]; Effects on bacterial plaque, influencing its growth and formation [ 106 ]; Effects on the immune system by helping to regulate the immune response and reduce inflammation [ 107 ]; Positive effects on wound healing by stimulating collagen production especially in the presence of small wounds or irritations caused by orthodontic devices [ 108 , 109 ]; Hydrating and soothing effects on skin and oral mucous membranes, improving patient comfort and reducing irritation [ 110 , 111 ]. …”
Section: Discussionmentioning
confidence: 99%
“…The onset of graft resorption was observed 1 week after placement and their degradation did not interfere with new bone growth nor caused side effects 282 . Other authors reported also a high angiogenic potential in addition to the aforementioned high rate of resorption and replacement for newly formed bone 283 . For example, a 24.5% of residual graft particles were reported after 4 months of implant insertion and graft with porcine xenograft 284 …”
Section: Grafting Material‐related Factors Altering Bone Metabolismmentioning
confidence: 99%
“…282 Other authors reported also a high angiogenic potential in addition to the aforementioned high rate of resorption and replacement for newly formed bone. 283 For example, a 24.5% of residual graft particles were reported after 4 months of implant insertion and graft with porcine xenograft. 284 Macroporous calcium phosphates like hydroxyapatite, biphasic calcium phosphate, or beta-tricalcium phosphate are synthetic bone graft substitutes.…”
Section: Porcine Collagenated Bonementioning
confidence: 99%
“…Various sources and formats of collagen have been proposed for periodontal and peri-implant tissues regeneration. As an example, due to their advantageous properties, such as good biocompatibility, hemostasis support, low antigenicity, degradation by specific enzymes, and chemotactic attraction of regenerative cells, collagen barrier membranes have been used for Guided Bone Regeneration (GBR) and Guided Tissue Regeneration (GTR) procedures for several years [ 26 ]. Moreover, collagen matrices are generally used for soft tissue regeneration, collagen sponges and cones for the stabilization of oral wounds and extraction sockets, and along with aesthetic medicine development, collagen is also used in its injectable form as a tissue stimulator [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the aim of this study was to investigate the effect of Dental SKIN BioRegulation (Guna S.p.a., Milan, Italy), an injectable medical device containing type I porcine collagen as the main component, on cultures of primary hGF. Indeed, collagen of porcine origin is already widely used in different clinical fields [ 31 , 32 , 33 ], including dentistry [ 26 , 34 , 35 ], because of its high similarity to human collagen and therefore, its excellent biocompatibility. The main focus of this research was to study the effect exerted by a coating of this injectable collagen on cell viability, proliferation, and cell migration for wound healing, as well as on the expression and activation of some mechanotransduction markers.…”
Section: Introductionmentioning
confidence: 99%